Letters patent, establishing the Court of Judicature at Prince of Wales' Island, Singapore, and Malacca, in the East-Indies, bearing date the twenty-seventh day of November, in the seventh year of the reign of George IV : Anno Domini, one thousand, eight hundred and twenty-six. - Pulau Pinang (State). Court of Judicature. (Malacca : Mission Press, 1827)
Mode of access: Internet.